2019
DOI: 10.3390/separations6040050
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids from Paracentrotus lividus Sea Urchin Shells Obtained via Rapid Solid Liquid Dynamic Extraction (RSLDE)

Abstract: Sea urchins (Echinodermata, Echinoidea) are good a source of bioactive compounds belonging to different classes of natural substances. The edible Mediterranean sea urchin Paracentrotus lividus is a renowned animal model for study in different fields of biology, but it is intensively harvested for high commercial value due to the delicacy of its gonads. Most studies have focused on the composition and the nutritional value of P. lividus gonads (the edible part), but little interest has been taken in the other b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…By comparing the spectra obtained for the extracts obtained through conventional maceration and the Naviglio method (data not shown for brevity), they showed that the extracts obtained under the same conditions (solvent, time, pH, ratio sample:solvent) with the Naviglio method had a higher content of coloring molecules compared to those obtained by maceration. Thus, it was concluded that the use of the Naviglio method allowed to obtain richer extracts in less time, as reported in the literature for other applications [38][39][40]. Figure 5 shows the spectra obtained from the analysis of the extracts of Opuntia ficus-indica (L.) Miller with the Naviglio method, which shows a better content of coloring molecules, even if only slightly, for the extract obtained with water.…”
Section: Resultssupporting
confidence: 52%
“…By comparing the spectra obtained for the extracts obtained through conventional maceration and the Naviglio method (data not shown for brevity), they showed that the extracts obtained under the same conditions (solvent, time, pH, ratio sample:solvent) with the Naviglio method had a higher content of coloring molecules compared to those obtained by maceration. Thus, it was concluded that the use of the Naviglio method allowed to obtain richer extracts in less time, as reported in the literature for other applications [38][39][40]. Figure 5 shows the spectra obtained from the analysis of the extracts of Opuntia ficus-indica (L.) Miller with the Naviglio method, which shows a better content of coloring molecules, even if only slightly, for the extract obtained with water.…”
Section: Resultssupporting
confidence: 52%
“…In fact, their proton spectra showed the signals related to fatty acid residues at δ: 5.46 Triglycerides in the oily extracts of G. lucidum were subjected to a common transesterification reaction, called alcoholysis. In transesterification, triglycerides react with methanol in the presence of a basic catalyst to form a mixture of glycerol and fatty acid methyl esters (FAMEs) [18]. FAMEs were identified and quantified via GC-MS in all samples.…”
Section: Resultsmentioning
confidence: 99%
“…NMR data suggest the presence, as main components, of triglycerides in the commercial sample of G. lucidum and in the extracts obtained as reported in previous sections. The triglycerides were submitted to a transesterification reaction with methanol in the presence of a basic catalyst (i.e., potassium hydroxide), as described by [18]. In this way, the fatty acids chains are released from glycerol skeleton and recombine with the alcohol to yield fatty acids methyl esters (FAMEs).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The extract contains arachidonic acid (ARA), 5,8,11,14,17-eicosapentaenoic acid (EPA) and 11-eicosenoic acids and their esters, as well as many polyunsaturated fatty acids (PUFA). These results mean that this extract is of great interest for possible future applications in the medical and/or nutritional field [23].…”
mentioning
confidence: 76%